Measurements in the Blood of BDNF for RA Patients and in Response to Anti-TNF Treatment Help Us to Clarify the Magnitude of Centrally Related Pain and to Explain the Relief of This Pain upon Treatment - Sture Forsgren; Ola Grimsholm; Tore Dalén; Solbritt Rantapää-Dahlqvist (Hindawi Limited, 2011)
Brain-derived neurotrophic factor (BDNF) is a neurotrophin with functions related to neuronal survival/proliferation processes and inflammation. BDNF is also an important central pain mediator. The levels of BDNF have been found to be high for RA patients with severe disease and to become lowered in response to anti-TNF treatment. New information says that the levels of BDNF in the blood parallel the BDNF concentrations in the brain and that BDNF can pass the blood-brain barrier. Furthermore, most of the circulating BDNF is produced in the brain. Habitual and regular exercise, in contrast to temporary exercise, does also lead to a lowering of BDNF blood levels. Both anti-TNF treatment and habitual and regular exercise do have pain-relieving effects. It might be that the pain-relieving effect of anti-TNF treatment is related to an affection of central neuronal regions, hereby influencing BDNF production. Measurements of BDNF in the blood help us to clarify the magnitude of centrally related pain for RA patients and help us to explain the relief of this pain in response to anti-TNF treatment.